Evaluating some in vitro bioactivities of ethanol extract from Ageratum conyzoidesin L. leaves collected in Vietnam in supporting skin wound treatment - Can, Nguyen Minh; Trinh , Trinh Thi My (Vietnam Journal of Biotechnology, 2024)
Ageratum conyzoides L. is widely used for the treatment of skin wound in some communities in Asia, Africa, and South America, including in Vietnam. In this study, we demonstrated that the 70% ethanol extract of A. conyzoides L. leaves collected in Bidoup National Park, Nui Ba, Lam Dong, Vietnam had some properties that would be advantageous for the treatment of skin wounds. Firstly, we found that the extract contained 64.9±2.58 mgGAE/gE polyphenols and 79.33±1.03 mgQE/gE flavonoids, and had antioxidant activity with the IC50 of 131.74±2.67 µg/mL. This extract was also proven to have antimicrobial activities against some pathogenic bacteria, including S. aureus, P. aeruginosa, E. faecalis, and E. coli. We also demonstrated that this extract could inhibit the generation of nitric oxide in LPS-activated Raw 264.7 cells, indicating its in vitro anti-inflammatory activity. And finally, for the first time, we found that the ethanol extract of A. conyzoides leaves could promote the proliferation of fibroblast NIH-3T3 cell line. All together, these findings support the traditional use of this plant in skin wound treatment.